A New Approach to Blasting Induced Ground Vibrations and Damage to Structures - Sasa Stojadinovic; Miodrag Zikic; Radoje Pantovic (Acta Montanistica Slovaca, 2011)
This article presents a new methodology for determination of causal connection between open pit blast induced ground vibration and damage to structures and liability for the damage. The basic hypothesis of the methodology is that damage is a result of joint action of both blasting and non-blasting related factors and that neither of these factors can be neglected regardless of its small strength. Additional hypothesis is that it is possible to calculate the percentage of blasting factor influence in total damage to structure. The methodology is primarily based on crack response monitoring approach but also defines and exploits the principle of partial liability which states that blaster should be held liable for the damage but only if the causality is proven and only to an amount equal to the percentage of blasting influence in total damage. The article gives guidelines for determination of causality and explains the procedure of blasting influence percentage calculation on an example.